Rayleigh wave propagation in isotropic sandy layer sliding over isotropic sandy semi-infinite medium with sliding contact - Madan, Dinesh Kumar; Kumar, Naveen; Rani, Annu (Zielona Góra: Uniwersytet Zielonogórski)
The present study aims to investigate Rayleigh wave propagation in an isotropic sandy layer overlying an isotropic sandy semi-infinite medium, with interface considered to be imperfect (slide contact and dislocation like model). Expressions for displacement components are obtained using the variable separation method. The dispersion frequency equation for the Rayleigh wave propagating in sandy media is derived using suitable boundary conditions.
Keywords: Rayleigh wave; sandy layer; imperfect interface; dispersion equation; phase velocity